Odpowiedzi

2010-04-03T11:47:37+02:00
A) an=3n-2
n=1 a1=3*1-2=1
n=2 a2=3*2-2=4 ciąg rosnący .
r=a2-a1=4-1=3

b) an=4-8n
n=1 a1=4-8*1=-4
n=2 a2=4-8*2=-12
r=-12-(-4)=-8 ciąg malejący .

c) an=1/2-3i1/2n
n=1 a1=1/2-3½*1=-3
n=2 a2=½ - 3½*2=-6½
r=-6½-(-3)=-3½ ciąg malejący .

d) an=1i1/3n
n=1 a1=1⅓
n=2 a2=2 i 2/3
r= 2 i 2/3- 1 i 1/3 = 1 i 1/3 ciąg rosnący .

e) an=n^2
n=1 a1=2
n=2 a2=4
r=4-2 =2 ciąg rosnący .

f) an=3n^2-1
n=1 a1=3*1=3
n=2 a2=6*1=6
r=6-3=3 ciąg rosnący .

g) an=n^2-1/2
n=1 a1= 1½
n=2 a2= 2*1½=3
r=3-1 ½ = 1½ ciąg rosnący .
2 1 2
2010-04-03T11:52:08+02:00
A) an=3n-2
an+1=3(n+1)-2=3n+3-2=3n+1
an+1-an=3n+1-(3n-2)=3n+1-3n+2=3>0
ciąg rosnący
b) an=4-8n
an+1=4-8(n+1)=4-8n-8=-8n-4
an+1-an=-8n-4-(4-8n)=-8n-4-4+8n=-8<0
ciąg malejący
c) an=1/2-3i1/2n
an+1=½-3½(n+1)=½-3½n-3½=-3½n-3
an+1-an=-3½n-3-(½-3½n)=-3½n-3-½+3½n=-3½<0
ciąg malejący
d) an=1i1/3n
an+1=1⅓(n+1)=1⅓n+1⅓
an+1-an=1⅓n+1⅓+1⅓n=1⅓>0
ciąg rosnący
e) an=n^2
an+1=(n+1)²=n²+2n+1
an+1-an=n²+2n+1-n²=2n+1
ciąg rosnący
f) an=3n^2-1
an+1=3(n+1)²-1=3(n²+2n+1)-1=3n²+6n+3-1=3n²+6n+2
an+1-an=3n²+6n+2-3n²-1=6n+1
ciąg rosnący
g) an=n^2-1/2
an+1=(n+1)²-½=n²+2n+1-½=n²+2n+½
an+1-an=n²+2n+½-(n²-½)=n²+2n+½-n²+½=2n+1
ciąg rosnący
1 5 1
2010-04-03T12:01:27+02:00
A) an = 3n -2
n=1 a1= 3* 1 -2=1 n= 2 a2= 3* 2 -2= 4 r= a² -a1= 4 -1=3
ciąg rosnący
b) an=4-8n
n=1 a1= 4 -8* 1= -4 n=2 a²= 4 -8* 2= -12 r= -12 -(-4) =-8
ciąg malejący

c) an= ½ -3 i ½n n=1 a1= ½ -3½* 1= -3
n=2 a² =½ - 3½ *2=-6½
r=-6½-(-3)=-3½
ciąg malejący

d) an=1i⅓n
n=1 a1=1⅓ n=2 a2=2 i ⅔ r= 2 i ⅔- 1 i ⅓ = 1 i ⅓
ciąg rosnący

e) an=n²
n=1 a1=2 n=2 a2=4 r=4-2 =2
ciąg rosnący

f) an=3n²⁻¹
n=1 a1=3*1=3 n=2 a2=6*1=6 r=6-3=3
ciąg rosnący

g) an=n²⁻½
n=1 a1= 1½ n=2 a2= 2*1½=3 r=3-1 ½ = 1½
ciąg rosnący